Philosophical aesthetics and cognitive science. Issue 1 (22nd June 2017) - Meskin, Aaron; Robson, Jon; Ichino, Anna; Goffin, Kris; Monseré, Annelies
Abstract : Philosophical aesthetics is the branch of philosophy which explores issues having to do with art, beauty, and related phenomena. Philosophers have often been skeptical about the place of empirical investigation in aesthetics. However, in recent years many philosophical aestheticians have turned to cognitive science to enrich their understanding of their subject matter. Cognitive scientists have, in turn, been inspired by work in philosophical aesthetics. This essay focuses on a representative subset of the areas in which there has been fruitful dialog between philosophical aestheticians and cognitive scientists. We start with some general topics in philosophical aesthetics—the definition of art and the epistemic status of aesthetic judgments. We then move on to discussing research concerning the roles that imagination and perception play in our aesthetic engagement. We conclude with a discussion of the emerging field of experimental philosophical aesthetics. WIREs Cogn Sci 2018, 9:e1445. doi: 10.1002/wcs.1445 This article is categorized under: Philosophy > Value